CLINICAL CHARACTERISTICS AND HAEMATOLOGICAL TRENDS IN PAEDIATRIC CASES OF DENGUE: A SINGLE CENTRE RETROSPECTIVE STUDY IN CHENNAI, TAMIL NADU. - Umapathy, Navin; Kousalya K. S; Narayanan, Kishore; Santhosh T; Mohammed, Syed (Student’s Journal of Health Research Africa, 2023)
Aim: This study is an attempt to perform an analysis about the clinical profile, serological indicators and predictors of dengue in children. Materials And Methods: The study was conducted including paediatric dengue admissions into a tertiary care teaching hospital in Chennai. Children under the age of 15 were included in the study. The demographic details, clinical characteristics and laboratory findings of these patients were collected by reviewing medical records and the data was entered into a standardized data collection sheet. Results: In the study, it was found that the mean age was 8.5 years. It was found that males (59.6%, n=34) were slightly more affected than females. On clinical examination, 24.5% of the subjects showed hepatomegaly and 5 cases of the subjects showed fluid accumulation in the abdomen. A majority (66.6%) of the subjects showed thrombocytopenia; with 31 having mild to moderate thrombocytopenia and 7 children having severe thrombocytopenia. An elevation of serum SGOT levels (>120 IU/L) was seen in about 80.7% of the patients. About 12% of the subjects showed hyponatremia. Conclusion: It is observed in our study that the presence of prodromal symptoms such as fever, arthralgia, vomiting, and lethargy does not preclude the diagnosis of dengue. Severe dengue was associated with a large decrease in platelet counts with severe thrombocytopenia leading to shock in the majority of the cases. Elevated liver enzymes were an added feature with the Transaminase levels being ten times the upper limit of normal. Hyponatremia was also a notable laboratory derangement. Recommendation: The over-the-counter (OTC) drug acetaminophen can help reduce muscle pain and fever. But if you have dengue fever, other OTC pain relievers like aspirin, ibuprofen (Advil, Motrin IB, others), and naproxen sodium (Aleve) should be avoided. These pain relievers can increase the risk of dengue fever bleeding complications.